The effect of heavy deformation on the precipitation in an Al-1.3Cu-1.0Mg-0.4Si wt.% alloy. (15th January 2020) - Thronsen, Elisabeth; Marioara, Calin D.; Sunde, Jonas K.; Minakuchi, Kazuhiro; Katsumi, Tetsuya; Erga, Iven; Andersen, Sigmund J.; Friis, Jesper; Marthinsen, Knut; Matsuda, Kenji; Holmestad, Randi
Abstract: This work has investigated the effect of the combination of natural ageing and 80% pre-deformation after solution heat treatment on precipitation during subsequent artificial ageing in an Al-1.3Cu-1.0Mg-0.4Si wt.% alloy. It was found that a combined use of atomic resolution aberration corrected high-angle annular dark-field scanning transmission electron microscopy and scanning precession electron diffraction enabled a detailed characterisation of precipitates in heavy pre-deformed materials. The dominant phase in the undeformed condition was the L phase. L was also found to be nucleated in the undistorted regions of the Al matrix in the pre-deformed conditions. Two phases with high aspect ratios were nucleated on dislocations: The C phase and a previously reported phase, which we named here the 'E phase'. The crystal structure of E was solved experimentally as monoclinic with core composition Mg6 Al2 Si2 Cu4, supported by density functional theory calculations. It was determined that the order of pre-deformation and natural ageing had an influence on the relative fractions of the aforementioned phases formed during artificial ageing. An increased fraction of C+E relative to L was found in the condition where the pre-deformation was applied after natural ageing as compared to the condition where the pre-deformation was applied before natural ageing. Graphical Abstract: Unlabelled Image Highlights: An advanced TEM for detailed characterisation of precipitates in pre-deformed materials is presented. The effect of natural ageing and pre-deformation on precipitation in terms of type and distribution is investigated. The crystal structure of a previously reported phase in pre-deformed Al-Mg-Si(-Cu) alloys is presented.